Islamic philosophy in the pedagogy of landscape architecture: case study on studio-based subject - Othman, Jamilah; Ahmad Sarkawi, Azila; Mansor, Mazlina (2011)
The pedagogy that responds to the Islamic philosophy is designed to produce better quality of intellectuals, professionals and scholars in the sense that the graduates are able to practise their work in accordance to the teaching of Islam. Thus, the Islamic values taught or stressed at both kulliyyahs (faculties) and departmental levels are hoped to produce insan (human) with acceptable adab (etiquette) and conduct. For instance, the International Islamic University Malaysia (IIUM) has realised the pedagogy by intertwining the tawhidic principle (declaration of one God) with all the courses offered by the university. The pedagogy explains the integration of Islamic revealed knowledge (e.g. tawhidic principles) with acquired knowledge (e.g. professional knowledge) as an approach to a holistic education. In relation to that, this paper intends to present the outcomes of such pedagogy as described in the programme‟s course outline and as applied to studio-based subjects. A case study was carried out involving one studio subject (ALA 1202 Landscape Design II) to evaluate the pedagogy of Islamic philosophy embedded in the subject. This is one of the core subjects designed for the Bachelor programme of Landscape Architecture (LA) offered by the Department of Landscape Architecture (DoLA) of Kulliyyah of Architecture and Environmental Design (KAED), IIUM. The Islamic philosophy had been integrated in the pedagogy of ALA 1202 Landscape Design II, while project brief and students‟ design outcomes became the measurement tools. The purpose of the case study was to evaluate the implementation of such pedagogy and how to improve its approach in the future teaching of studio-based subjects. Descriptive evaluation was used to assess the implications of the philosophical teaching. The findings show that the Islamic philosophy was introduced to the pedagogy through (i) etiquette of delivering the lesson, (ii) mode of the written projects‟ brief and finally, (iii) expected outcomes through problem solving of design projects. Results show that the pedagogy that based on the holistic education has contributed to several implications. This concludes that the implementation of the Islamization of human knowledge can be traced in the approach of the pedagogy of landscape architecture in this department. In addition, the findings provide a larger picture on the evolution of new paradigm in the education system of the 21st century by integrating the Islamic philosophy to the pedagogy.